The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1809-4392201305953
|View full text |Cite
|
Sign up to set email alerts
|

Importance of anatomical leaf features for characterization of three species of Mapania (Mapanioideae, Cyperaceae) from the Amazon Forest, Brazil

Abstract: Mapania belongs to Mapanioideae, a quite controversial subfamily in Cyperaceae due to the existence of unusual characters in both reproductive and vegetative organs. The genus is represented by seven species in Northern Brazil but taxonomic valuable information related to the leaf organs is still unknown. The present study aimed the anatomical description of the leaf organs (either basal leaves or cataphylls and involucral bracts) of three representative Brazilian species of Mapania. Samples of cataphylls, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Leaf samples were progressively dehydrated in an ethanol series (50%, 70%, 85%, 95%, and 100%) and infiltrated with warm paraffin; leaf transverse sections (8–12 μm) thickness were then cut using a rotary microtome (Leica RM2255, Germany). Lignified tissues were red‐stained using Safranin and non‐lignified cell walls were blue‐stained with Fast Green to Blue stain, leaf sections were then mounted in slides and sealed with neutral glue (Garcia, Potiguara, Kikuchi, Demarco, & Aguiar‐Dias, ; Ocheltree, Nippert, & Prasad, ; Silva, Alves, & Coan, ; Sobrado, ). The slides were observed and photographed under a light microscope (Leica DM2500, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Leaf samples were progressively dehydrated in an ethanol series (50%, 70%, 85%, 95%, and 100%) and infiltrated with warm paraffin; leaf transverse sections (8–12 μm) thickness were then cut using a rotary microtome (Leica RM2255, Germany). Lignified tissues were red‐stained using Safranin and non‐lignified cell walls were blue‐stained with Fast Green to Blue stain, leaf sections were then mounted in slides and sealed with neutral glue (Garcia, Potiguara, Kikuchi, Demarco, & Aguiar‐Dias, ; Ocheltree, Nippert, & Prasad, ; Silva, Alves, & Coan, ; Sobrado, ). The slides were observed and photographed under a light microscope (Leica DM2500, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…For the Neotropical area, besides the taxonomic studies and new species described in Hypolytrum and Mapania, which is the only closely related genus that also occurs on the American continent (Koyama 1969(Koyama , 1970Simpson 1992Simpson , 1996Alves 2003;Alves et al 2002aAlves et al , 2002bAlves et al , 2004, important morphological evidence, evolutionary interpretations and information about diversity and geographical distribution have been published (Koyama 1966;Alves et al 2000Alves et al , 2002cAlves et al , 2003Alves et al , 2009Alves et al , 2014Coan et al 2008Coan et al , 2010Rodrigues & Estelita 2009;Silva et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…; Silva et al. ). This does not conform to the expectation, since leaf organs last longer—while scapes usually dry after seed dispersal—and are theoretically less conservative and more susceptible to environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al. () showed that, at the infrafamiliar level, the leaf and involucral bract anatomy has some importance in distinguishing M . sect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation